1979
DOI: 10.1099/00221287-114-1-125
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of Pseudomonas putida on Chlorinated Aliphatic Acids and its Dehalogenase Activity

Abstract: Two strains of Pseudomonasputida, S3 and P3, were shown to contain dehalogenase activity against monochloroacetate, dichloroacetate, 2-monochloropropionate and 2,2'-dichloropropionate but differed markedly in their levels of enzyme activity. Strain S3 had activities of less than 1 pmol substrate converted (mg protein)-l h-l and was unable to grow on any of nine chlorinated compounds tested. Strain P3 had enzyme activities 10 to 40 times greater than those of strain S3 but was capable of growth only on 2-monoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 17 publications
8
72
0
Order By: Relevance
“…Growth on MCA in closed culture was not obtained since MCA at the initial concentrations usually used (0.5 g carbon 1-l) was inhibitory, and indeed growth was not obtained at 10-fold lower concentrations. This was similar to the effect of halogenated acetic acids on the growth of Pseudomonas putida PP3 previously reported (Slater et al, 1979); however, growth on these compounds can be obtained as long as continuous-flow culture systems are used to prevent the accumulation of high, toxic concentrations of halogenated alkanoic acids (Slater et al, 1979). This was achieved for Pseudomonas sp.…”
Section: R E S U L T Ssupporting
confidence: 59%
See 2 more Smart Citations
“…Growth on MCA in closed culture was not obtained since MCA at the initial concentrations usually used (0.5 g carbon 1-l) was inhibitory, and indeed growth was not obtained at 10-fold lower concentrations. This was similar to the effect of halogenated acetic acids on the growth of Pseudomonas putida PP3 previously reported (Slater et al, 1979); however, growth on these compounds can be obtained as long as continuous-flow culture systems are used to prevent the accumulation of high, toxic concentrations of halogenated alkanoic acids (Slater et al, 1979). This was achieved for Pseudomonas sp.…”
Section: R E S U L T Ssupporting
confidence: 59%
“…In addition, particularly in those strains containing two or more dehalogenases, it is possible that these organisms will provide an opportunity to study the pattern of complex regulatory mechanisms, their interaction and, perhaps, the evolution of control mechanisms. Previous studies (Slater et al, 1979;Weightman & Slater, 1980) have shown that the organism's growth rate significantly affects dehalogenase specific activities, with a pattern characteristic of catabolic enzymes (Clarke 8z Lilly, 1969;Dean, 1972).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activity stain PAGE, utilizing Ag+ to precipitate free halide ions in regions of dehalogenase activities, has been employed to identify electrophoretically distinguishable 2-haloacid halidohydrolases (Slater et al, 1979;Hardman & Slater, 1981 ;Allison et al, 1983). The same technique was used by Scholtz et al (1988) to visualize one of the dehalogenase activities in Arthrobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Soil samples were obtained from a discharge point at an industrial site where haloalkanes had been used for several decades. Soil samples (5 g) were incubated in 250 ml screwtop bottles containing 20 ml defined growth medium (Slater et al, 1979) at pH 7.0 containing modified quantities of (1-I): Na2HP0,.12 H,O, 4 g; KH2P0,, 1 g; NaHCO,, 1 g; yeast extract, 20 mg; CoC12.6H20, 100 pg; NiC12.6 H 2 0 , 20 pg; and H3B03, 100 pg. 1-Chlorobutane was added as the sole carbon and energy source at 0.9 g 1-'.…”
Section: Methodsmentioning
confidence: 99%